(untitled) (قضايا سياسية, 2023)
This research attempts to study and analyze the political and economic conditions imposed by the consequences and repercussions of the Russian war on Ukraine, by focusing on the policy adopted by the Algerian government, especially with regard to government orientations and official visions aimed at positioning between the two sides of the conflict in the European continent. This paper highlights Algeria’s potential role in the market of European gas as the third largest resource for the continent, as well as its constant need for the European countries’ exports of foodstuffs. The research concludes that Algeria, despite the affirmation of its unwavering partnership with the Russian Federation, has kept an equal distance between the sides of the conflict in the continent.